(untitled) (Research, Society and Development, 2020)
The purpose of this article is to think about how the modes of resistance arise in the context of a public school. The cartographic investigation method produced the written material in the monitoring of the realized interventions and in the chance of encounters. Cartography here, conceived as an experimentation attitude when researching the territory in constant movement, also started to move, mindfully mapping the forces existing in each encounter. It was asked: which power relations circulate and help to compose this territory? What causes acts of resistance? How do these acts promote a production of desire and creative tactics? The results show that, when facing the appearances and the functioning of a power that tries to subjugate, practices of self and appropriation of the real are enhanced by resistance and creation, even if it is necessary to fight daily micro-confrontations, opening breathing spaces for a possible living school in difficult times. A writing that is not completed, but that opens rhizomatically, launching itself to constant updating.